Development of Canva-based Website Media on Class X for Virus Topic in Biology Learning - Nurhidayah, Nurhidayah; Syamswisna, Syamswisna; Titin*, Titin; Haruno, Mai (Jurnal Pendidikan Sains Indonesia, 2024)
The current technological advancements have a crucial role in education, bringing about innovations in the learning process. One form of innovation is using website media as a learning tool. This research aims to assess the feasibility and students' responses towards a Canva-based website learning media on viruses for high school X grade. The study follows the research and development approach using the ADDIE method. In this research using random sampling technique. The sample research used 10 students of XI MIPA 2 at SMAN 2 Teluk Keramat. Instruments utilized include validation sheets and student response questionnaires. The data analysis calculates the validation using Aiken's V formula and average score of student response and classifies into availablecategories. Validation was carried out by 2 biology lecturers at Untan and 3 biology teachers. The validation analysis using Aiken's V yielded a score of 0.89 for the Canva-based website media on virus topic, categorized as valid. The questionnaire analysis revealed an average response rate of 83.82%, indicating a very strong category of acceptance. Based on these results, it can be concluded that the Canva-based website media is suitable for use as a learning media on class X for virus topic